Beam cleaning effects in multimode GRIN-fiber Raman lasers and amplifiers. (March 2020) - Kuznetsov, A.G.; Nemov, I.N.; Wolf, A.A.; Kablukov, S.I.; Babin, S.A.; Chen, Yizhu; Yao, Tianfu; Leng, Jinyong; Zhou, Pu
Abstract: Raman conversion in multimode GRIN fibers is accompanied by sufficient improvement of the output beam quality in comparison with that for pump radiation, which offers opportunities to create amplifiers and lasers of new type based on directly 9xx-nm diode pumped passive GRIN fibers, which may operate at almost any wavelength in transmission window (0.95-2 micron) of silica fibers. Here we review experimental results and physical mechanisms leading to the beam quality improvement (beam cleaning) in multimode Raman lasers and amplifiers, including effects of Raman gain, fiber Bragg gratings and Rayleigh backscattering feedback in GRIN fibers.